Philosophy of Right without Foundations in Richard Dien Winfield's Critical Hegelianism - Charilaos Stampoulis (International Society of Philosophy and Cosmology, 2022)
This article aims to explore and lay out crucial aspects of the interpretation of the Hegelian philosophy offered by the American thinker Richard Dien Winfield. Winfield works out an innovative line of interpretation that decisively ties Hegel to a non-foundational type of philosophical epistemology with significant consequences concerning the concept of objectivity in both theoretical and practical philosophical investigation. The article attempts to reconstruct this line of interpretation and assess its argumentative force, in view of an array of epistemological problems regarding theory construction in political philosophy. On this account, the principal question is whether the special brand of epistemological non-foundationalism ascribed by Winfield to Hegel is actually in a favorable position to successfully tackle with these problems.